Using Concept Maps to Aid Reading Comprehension in a High School Biology Classroom - Cynthia H. Joseph (Networks: An Online Journal for Teacher Research, 2002)
Teachers are always looking for innovative ways to help students improve their reading comprehension in subject matter materials. One popular method is the use of graphic organizers such as concept maps. This study examined the use of concept maps to aid reading comprehension of science articles by 10th grade students (n=49) in a Florida high school biology classroom. By comparing scores on reading comprehension tests for two articles, one read without concept mapping and one read while doing a concept map organizing key themes and ideas in the article, significant evidence for the effectiveness of concept mapping was found for one of two groups of participants. These results call for additional investigations into the effects of concept mapping on reading comprehension.